Cardiovascular and Muscular Consequences of Work-Matched Interval-Type of Concentric and Eccentric Pedaling Exercise on a Soft Robot - Flück, Martin (Front Physiol, 2017)
Eccentric types of endurance exercise are an acknowledged alternative to conventional concentric types of exercise rehabilitation for the cardiac patient, because they reduce cardiorespiratory strain due to a lower metabolic cost of producing an equivalent mechanical output. The former contention has not been tested in a power- and work-matched situation of interval-type exercise under identical conditions because concentric and eccentric types of exercise pose specific demands on the exercise machinery, which are not fulfilled in current practice. Here we tested cardiovascular and muscular consequences of work-matched interval-type of leg exercise (target workload of 15 sets of 1-min bipedal cycles of knee extension and flexion at 30 rpm with 17% of maximal concentric power) on a soft robotic device in healthy subjects by concomitantly monitoring respiration, blood glucose and lactate, and power during exercise and recovery. We hypothesized that interval-type of eccentric exercise lowers strain on glucose-related aerobic metabolism compared to work-matched concentric exercise, and reduces cardiorespiratory strain to levels being acceptable for the cardiac patient. Eight physically active male subjects (24.0 years, 74.7 kg, 3.4 L O2 min(−1)), which power and endurance performance was extensively characterized, completed the study, finalizing 12 sets on average. Average performance was similar during concentric and eccentric exercise (p = 0.75) but lower than during constant load endurance exercise on a cycle ergometer at 75% of peak aerobic power output (126 vs. 188 Watt) that is recommended for improving endurance capacity. Peak oxygen uptake (−17%), peak ventilation (−23%), peak cardiac output (−16%), and blood lactate (−37%) during soft robotic exercise were lower during eccentric than concentric exercise. Glucose was 8% increased after eccentric exercise when peak RER was 12% lower than during concentric exercise. Muscle power and RFD were similarly reduced after eccentric and concentric exercise. The results highlight that the deployed interval-type of eccentric leg exercise reduces metabolic strain of the cardiovasculature and muscle compared to concentric exercise, to recommended levels for cardio-rehabilitation (i.e., 50–70% of peak heart rate). Increases in blood glucose concentration indicate that resistance to contraction-induced glucose uptake after the deployed eccentric protocol is unrelated to muscle fatigue.